2004
DOI: 10.1002/adma.200305680
|View full text |Cite
|
Sign up to set email alerts
|

Multibit Memory Using Self‐Assembly of Mixed Ferrocene/Porphyrin Monolayers on Silicon

Abstract: During the past decade there has been intense interest in developing molecular-based devices for applications in electronics, including memory.[1±4] Among the various approaches towards building devices that incorporate molecules, the hybrid silicon/molecular approach is attractive as a transition technology because it leverages certain advantages afforded by a molecule-based active medium with the vast infrastructure of traditional metal±oxide±semiconductor (MOS) technology. Recently, we demonstrated that sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
106
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(106 citation statements)
references
References 18 publications
0
106
0
Order By: Relevance
“…Chemical functionalization of silicon oxide surfaces with silane molecules is an important technique for a variety of device fabrication. [20][21][22] One of the main interests is the formation of silanized glass surfaces and their use in non-linear optical devices, 23 or in sensor applications. 24,25 In 1980 Sagiv published a seminal paper reporting the reaction of chloro-and alkoxy-silanes (RSiCl 3 and RSi(OR 0 ) 3 with R = C 18 H 37 and R 0 = Me or Et) with hydroxyl-terminated surfaces of oxidized substrates to afford a covalent molecular layer.…”
Section: Organosilane Based Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical functionalization of silicon oxide surfaces with silane molecules is an important technique for a variety of device fabrication. [20][21][22] One of the main interests is the formation of silanized glass surfaces and their use in non-linear optical devices, 23 or in sensor applications. 24,25 In 1980 Sagiv published a seminal paper reporting the reaction of chloro-and alkoxy-silanes (RSiCl 3 and RSi(OR 0 ) 3 with R = C 18 H 37 and R 0 = Me or Et) with hydroxyl-terminated surfaces of oxidized substrates to afford a covalent molecular layer.…”
Section: Organosilane Based Layersmentioning
confidence: 99%
“…For many applications, whether a monolayer, or rather an ill-defined multilayer is formed, is not a significant issue. On the other hand, when using these systems as the base layer upon which truly molecular devices will be fabricated, 22 lack of control in the SAM growth can be a major concern. Another challenge with using organosilanes for modifying SiO 2 surfaces is the lack of stability in basic media.…”
Section: Organosilane Based Layersmentioning
confidence: 99%
“…[23][24][25] As comprehensively reviewed elsewhere, [26][27][28][29][30] and as discussed to an introductory level in a following section of this review (Section 2), formation of molecular layers on crystalline silicon surfaces without an intervening oxide layer is an extremely appealing approach toward robust layers on a surface. [31][32][33][34] Silicon-carbon linked monolayers on silicon substrates are expected to complement and/or extend the applications of the currently most relevant technological material 35 toward the development of atomic scale devices, [36][37][38] diverse molecular devices, [39][40][41][42][43][44][45][46][47][48] and well-defined sensing interfaces. [49][50][51][52][53] The following sections are intended as an up-to-date presentation of the topic of molecular layers on non-oxidized silicon surfaces.…”
Section: Jason B Harpermentioning
confidence: 99%
“…For example, nanoscale molecularelectronic circuits consisting of a molecular monolayer of rotaxanes (~1100 molecules) have been successfully fabricated and tested by Yong Chen and his co-workers [2]. Recently Lindsey, Bocian and Mirsa have demonstrated that selfassembled monolayers of electrochemical-active molecules (such as porphyrin and ferrocene) on silicon or gold look to be a promising alternative for next generation memories [3,4]. We have demonstrated surface-mounted ferrocene using covalent immobilisation of an alcohol substituted ferrocene derivative to a pre-assembled single-walled carbon nanotubes directly anchored to a silicon (100) surface (SWCNT-Si) [5], which gave a much higher surface concentration of ferrocenemethanol molecules; about 500-1000 times greater than the experimentally measured coverage of ferrocene directly attached to flat Si(100) surfaces.…”
Section: Introductionmentioning
confidence: 99%